1994
DOI: 10.1254/jjp.65.257
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis of Canine Femoral Artery Thrombus by a Novel Modified Tissue-Type Plasminogen Activator (E6010).

Abstract: ABSTRACT-The thrombolytic activity of a novel modified tissue-type plasminogen activator (t-PA) (E6010) was examined in a canine model with copper coil-induced femoral artery thrombus. This model, in which thrombolytic activity can be easily and directly quantified by determining changes in thrombus weight, should be useful for comparing the activities of various thrombolytic agents. Using this model, the present study showed that the thrombolytic activity of bolus intravenous injection of E6010 was identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…One of such t-PA molecules in which Cys84 in the E-domain is replaced by Ser, has a half-life in man of more than 20 min, as compared to 6 min for native t-PA. This molecule has been used successfully for bolus administration in a canine femoral artery thrombosis model (14) and in a multicenter trial in patients with acute myocardial infarction (15).…”
Section: Mutants and Variants Of Tissue-type Plasminogen Activatormentioning
confidence: 99%
“…One of such t-PA molecules in which Cys84 in the E-domain is replaced by Ser, has a half-life in man of more than 20 min, as compared to 6 min for native t-PA. This molecule has been used successfully for bolus administration in a canine femoral artery thrombosis model (14) and in a multicenter trial in patients with acute myocardial infarction (15).…”
Section: Mutants and Variants Of Tissue-type Plasminogen Activatormentioning
confidence: 99%
“…Recovery to the level before injection in both groups 24 hours after the operation suggested that thrombolytic drugs only had a temporary, rather than long-term, influence on blood coagulation, similar to studies of alteplase in other canine femoral artery thrombus models. 47 …”
Section: Discussionmentioning
confidence: 99%